The Relationship of the Nurse's Percepted Work Rotation With Motivation to Work at Peusangan Puskesmas Bireuen District - Alhuda; Roslaini (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2022)
Conducive working conditions can be used as an indicator of the success of job rotation. rotation must be based on interest, employees must have the ability and skills. The purpose of this study was to examine the relationship between job rotation perceived by nurses and work motivation at the Peusangan Public Health Center, Bireuen Regency. This type of research is quantitative with a correlation design using a cross sectional approach. The technique of taking the sample in this research is random sampling technique. Respondents in this study were 50 respondents to the nurses of the Peusangan Bireuen Health Center. This study uses an instrument that has been developed by the researcher based on nurse rotation including rewards, challenges, responsibilities, and development. While the work motivation instruments include fixed motivation, moderate motivation and increased motivation. The results showed that 68% of nurses had experienced work rotation, while the remaining 32% of nurses had never experienced work rotation. there is no significant relationship between work rotation perceived by nurses and work motivation where p - Value (0.423) > (0.05). Job rotation perceived by nurses is a common thing that has been experienced by 68% of nurses. The work motivation of puskesmas nurses is on good criteria.